2004
DOI: 10.1002/pds.954
|View full text |Cite
|
Sign up to set email alerts
|

Drug counselling in pregnancy: an opinion survey of French community pharmacists

Abstract: The present study shows that French community pharmacists do not always give appropriate advice to pregnant women. As primary health care providers, pharmacists have to improve counselling regarding drug use in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 9 publications
2
14
0
2
Order By: Relevance
“…It has been shown that CPs do not always give appropriate advice to pregnant women. 7 This could be explained by several points. First, initial training about drug use in pregnancy is insufficient during pharmaceutical and medical studies (2h within 6 years for CPs and 3.5h within 9 years for GPs).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CPs do not always give appropriate advice to pregnant women. 7 This could be explained by several points. First, initial training about drug use in pregnancy is insufficient during pharmaceutical and medical studies (2h within 6 years for CPs and 3.5h within 9 years for GPs).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, all studies were descriptive and cross-sectional with samples of 110-276 pharmacists, mainly practicing in community pharmacies. Three out of four studies presented various scenarios to pharmacists and questioned them about their counselling on pharmacological as well as non-pharmacological treatment, and referral to a physician [49][50][51].…”
Section: Community Pharmacists' Counselling Of Pregnant Womenmentioning
confidence: 99%
“…However, very few studies have investigated pharmacists' counselling of pregnant women (Appendix 1). The findings showed that pharmacists did not always give appropriate information to pregnant women (Schrempp et al, 2001;Lyszkiewicz et al, 2001;Damase-Michel et al, 2004). They often referred women to a physician or recommended homeopathy (Lyszkiewicz et al, 2001;Damase-Michel et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Pharmacists felt uncertain if disagreeing with the physician and they needed additional education ( (Schrempp et al, 2001;Lyszkiewicz et al, 2001;Damase-Michel et al, 2004;Grincevičiene et al, 2015;Bains at el., 2014). In spite of such findings, the International Pharmaceutical Federation (FIP) proposed a policy statement in 2013 which declares certain interventions where pharmacists can make a significant contribution in improvement of maternal health.…”
Section: Introductionmentioning
confidence: 97%